Role of Calcium Sulphate in Metigating the Adverse Effect of NaCl in Some of Growth Parameters of (Triticum aestivum L.)C.V. Fateh in Hydroponic Culture - AL-Rahmani, Hana Fadil Khamis; AL-Mufty, Zena Abd EL-Monaam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was carried out to study the tolerance degree of wheat Triticum aestivum L. C. V. AL-Fateh to NaCl (0,20,50,70,100) mM by using CaSO4 (1,5,10) mM in hydroponic culture.  The results showed that the adverse effect of NaCl on some growth parameters such as chlorophyll concentration , soluble carbohydrates and protein content in shoot and root systems were increased with increase of NaCl concentration in growth medium , But these effects are reduced  by using CaSo4 to ellivate the stress of NaCl . The best results were obtained by using 5mM of CaSO4 with 50mM of NaCl and 10mM of CaSO4 with 100mM of NaCl in these concentrations the chlorophyll , soluble carbohydrates and protein contents were raised to the level of control treatment without statistical difference